A pilot study of a mixed-method approach to design an ED-based peer mHealth referral tool for HIV/HCV and opioid overdose prevention services. (1st September 2022) - Knaub, Ross J.; Evans, Julie; Yang, Cui; Roura, Raúl; McGinn, Tanner; Verschoore, Benjamin; Ricketts, Erin P.; Rothman, Richard E.; Latkin, Carl A.; Hsieh, Yu-Hsiang
Abstract: Background: The intersecting epidemics of opioid misuse, injection drug use, and HIV/HCV have resulted in record overdose deaths and sustained high levels of HIV/HCV transmissions. Literature on social networks suggests opportunities to connect people who use drugs (PWUD) and their peers to HIV/HCV and opioid overdose prevention services. However, little evidence exists on how to design such peer referral interventions in emergency department (ED) settings. Methods: A mixed-method study was conducted to assess the feasibility of an mHealth-facilitated 'patient to peer social network referral program' for PWUD. In-depth interviews (IDIs) and quantitative surveys were conducted with urban ED patients (n = 15), along with 3 focus group discussions (FGDs) (n = 19). Results: Overall, 34 participants were enrolled (71 % males, 53 % Black). 13/15 IDI participants reported a history of opioid overdose; all had witnessed overdose events; all received HIV/HCV testing. From survey responses, most would invite their peers for HIV/HCV testing and naloxone training; and anticipated peers to accept referrals (HIV: 60 %, HCV: 73 %, naloxone: 93 %). Qualitative data showed PWUD shared health-related information with each other but preferred word of mouth rather than text messages. Participants used smartphones regularly and suggested using Internet advertising for prevention services. Participants expressed enthusiasm for ED-based peer mHealth referral platform to prevention services, as well as referring their peers to proposed services, with monetary incentives. Conclusion: ED-based peer referral intervention to HIV/HCV testing and naloxone training was viewed favorably by PWUD. Frequent smartphone use among PWUD suggests that the medium could be a promising mode for peer referral. Highlights: This preliminary study revealed ED peer referral to HIV/HCV testing & naloxone training was viewed favorably by PWUD. All subjects had either received naloxone training or witnessed naloxone use on PWUD. Social media could be a useful mode to engage more PWUD with smartphone access. Social media and internet campaigns could be a promising mode for peer referral. Financial incentives likely improve peer referral to prevention services.